Nitrogen Sidedress Directed by Corn Canopy Reflectance for Manured Fields. (1st September 2019) - Montealegre, Juan Pablo Garcia; Wortmann, Charles; Ferguson, Richard; Shaver, Timothy; Schepers, James
Abstract : Fertilizer‐N equivalence of applied organic N is poorly predicted, often resulting in overapplication of fertilizer‐N. Research was conducted for continuous‐corn ( Zea mays L.) at an irrigated location in eastern Nebraska with the objective of adapting variable rate in‐season N (ISN) application directed by remote sensing of crop canopy reflectance for manure‐applied fields. Beef ( Bos taurus ) feedlot manure was applied in 2015 at 0, 37, and 74 Mg ha –1 to main plots, and 0 to 120 kg ha –1 yr –1 pre‐plant N (PPN) was applied in 30‐kg increments to subplots. Sub‐subplot treatments were with and without ISN applied at V12. The ISN rates determined at V8 to V12 were well correlated, indicating that earlier canopy sensing can be used for later ISN application. The mean yield increase with ISN was 3.3 Mg ha –1 . The crop responded to ISN within 10 d of application, but recovery was incomplete by tasseling when N deficiency stress was severe. If severe N stress occurs, the crop may benefit from ISN application before V12 for more recovery time. The mean ISN rate was 23% less with manure compared with no manure application. The results indicate a need to apply some ISN even when a sufficiency index indicated adequate N. The harvest index was greater with ISN compared with no ISN. Mean agronomic efficiency of ISN was 29.4 kg yield gain kg –1 N applied. The sensor‐ISN for corn was sensitive to manure N availability and is a means to achieve manure N use efficiency with high productivity. Core Ideas Availability of applied organic N to crop uptake is poorly predicted. Canopy reflectance can account for manure N supplied to the crop. Agronomy efficiency of sidedress N directed by crop reflectance is high for manured fields